Practical cataloguing : - Welsh, Anne (Neal-Schuman Publishers, imprint of American Library Association, 2012)
This textbook explores how RDA elements can be incorporated into MARC21. Topics include: an introduction to catalogues and cataloguing standards, publication formats and bibliographic elements, access points and headings, a summary which outlines the major issues and many others.